The impact of sensation seeking on the relationship between attention deficit/hyperactivity symptoms and severity of Internet addiction risk. Issue 1 (30th July 2015) - Dalbudak, Ercan; Evren, Cuneyt; Aldemir, Secil; Taymur, Ibrahim; Evren, Bilge; Topcu, Merve
Abstract: The aim of this study was to investigate the relationship of attention deficit/hyperactivity symptoms (ADHS) with severity of Internet addiction risk (SIAR), while controlling the effects of variables such as depression, anxiety, anger, sensation seeking and lack of assertiveness among university students. Cross-sectional online self-report survey was conducted in two universities among a representative sample of 582 Turkish university students. The students were assessed through the Addiction Profile Index Internet Addiction Form Screening Version (BAPINT-SV), the Psychological Screening Test for Adolescents (PSTA) and the Adult Attention deficit/hyperactivity disorder Self-Report Scale (ASRS). The participants were classified into the two groups as those with high risk of Internet addiction (HRIA) (11%) and those with low risk of Internet addiction (IA) (89%). The mean age was lower in the group with HRIA, whereas depression, anxiety, sensation seeking, anger, lack of assertiveness and ADHS scores were higher in this group. Lastly, a hierarchical regression analysis suggested that severity of sensation seeking and ADHS, particularly attention deficiency, predicted SIAR. The severity of sensation seeking and ADHS, particularly attention deficit symptoms, are important for SIAR. Awareness of sensation seeking among those with high ADHS may be important in prevention and management of IA among university students. Highlights: SIAR is associated with anger, sensation seeking, lack of assertiveness, anxiety, depressive symptoms and ADHS. However, the main finding of the present study is that sensation seeking and severity of ADHS were still associated with the SIAR even after controlling other variables. The severity of sensation seeking and ADHS, particularly attention deficit symptoms, are important for SIAR among university students. Awareness of sensation seeking among those with high ADHS may be important in prevention and management of IA among university students.